2016
DOI: 10.1016/j.watres.2016.09.052
|View full text |Cite
|
Sign up to set email alerts
|

Biogas production from hydrothermal liquefaction wastewater (HTLWW): Focusing on the microbial communities as revealed by high-throughput sequencing of full-length 16S rRNA genes

Abstract: Hydrothermal liquefaction (HTL) is an emerging and promising technology for the conversion of wet biomass into bio-crude, however, little attention has been paid to the utilization of hydrothermal liquefaction wastewater (HTLWW) with high concentration of organics. The present study investigated biogas production from wastewater obtained from HTL of straw for bio-crude production, with focuses on the analysis of the microbial communities and characterization of the organics. Batch experiments showed the methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(32 citation statements)
references
References 63 publications
3
29
0
Order By: Relevance
“…Only our previous study made such analysis and found Firmicutes was dominant in the microbial community during AD of HTLWW [10], which was consistent with the present study. It should be noted that Proteobacteria was also dominant in the samples of the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Only our previous study made such analysis and found Firmicutes was dominant in the microbial community during AD of HTLWW [10], which was consistent with the present study. It should be noted that Proteobacteria was also dominant in the samples of the present study.…”
Section: Discussionsupporting
confidence: 93%
“…However, the HTLWW in the above study was not well characterized. Our recent publication showed that the methane yield of HTLWW obtained from HTL of straw at 27 days can be enhanced by organic solvent extraction, and the HTLWW conversion efficiency was 53% [10]. A biohythane production [11] for high energy recovery and carbon recovery is 79.0 and 67.7%, respectively, from HTL cornstalk, but it was limited by low hydrogen fermentation performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrothermal liquefaction (HTL) is a promising and attractive thermo-chemical conversion technology, which can directly transform wet biomass to valuable biocrude oil at high temperatures (200°C-370°C) and pressures (20-23 MPa) [44] , which can be further refined into transportation fuels. However, PHWW is created as one of the main by-products during this process [45] .…”
Section: Post-hydrothermal Liquefaction Wastewatermentioning
confidence: 99%
“…In particular, how RS AD microbial populations respond to different FFs and OLRs is largely unknown, especially for shock loads (Mei et al , ). Some studies have investigated microbial communities in RS AD (Nakakihara et al , ; Yan et al , ; Chen et al , ), but the range of conditions has been limited. Further, no studies have assessed the effect of different FFs on AD microbial community conditions.…”
Section: Introductionmentioning
confidence: 99%